2013
DOI: 10.4236/ojanes.2013.33035
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma Anesthetic Management

Abstract: Pheochromocytomas are catecholamine producing tumors and although uncommon present a great challenge to the anesthesiologist since it has nonspecific clinical symptoms and risk of critical events, including death when not previously diagnosed. Clinical manifestation is variable, unspecific and depends on the catecholamine production profile. The classic triad of headache, palpitation and diaphoresis is present in up to 70% of the cases and only 50% have sustained hypertension. The best approach for pheochromoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…There are relatively little data published on the management of mediastinal pheochromocytomas; however, the treatment of choice is surgical resection, being curative in the majority of cases. 5,6 The authors' literature search revealed no published data to date discussing the anesthetic management of a secreting cardiac pheochromocytoma. Patients with a diagnosed pheochromocytoma usually are referred to an endocrine surgeon who often works with an anesthesiologist with expertise in the perioperative management of those patients.…”
Section: Discussionmentioning
confidence: 96%
“…There are relatively little data published on the management of mediastinal pheochromocytomas; however, the treatment of choice is surgical resection, being curative in the majority of cases. 5,6 The authors' literature search revealed no published data to date discussing the anesthetic management of a secreting cardiac pheochromocytoma. Patients with a diagnosed pheochromocytoma usually are referred to an endocrine surgeon who often works with an anesthesiologist with expertise in the perioperative management of those patients.…”
Section: Discussionmentioning
confidence: 96%
“…Clinical signs and symptoms, biochemical testing, and radiographic testing are used to make the diagnosis. 5 In the anamnesis, we obtained complaints of dizziness and palpitations. On physical examination of the patient, it found sustained high blood pressure with no apparent cause.…”
Section: Discussionmentioning
confidence: 99%
“…The stress of surgery and anesthesia can trigger hypertensive crises and other catecholamine-induced adverse events, leading to intraoperative mortality. [7] In our case, the differential diagnosis for the sudden intraoperative hypertensive crisis after tourniquet release included inadequate anesthesia, iatrogenic causes (e.g., accidental administration of vasopressors), severe hypercarbia, increased intracranial pressure (ICP), myocardial ischemia, bladder distension, thyroid storm, and pheochromocytoma. The patient did not report and discomfort or pain from the surgery making inadequate anesthesia or analgesia unlikely.…”
Section: Discussionmentioning
confidence: 99%